THE INFLUENCE OF WORK MORALE ON ORGANIZATIONAL COMMITMENT OF POLICE MEMBERS IN THE DIRECTORATE OF DRUG INVESTIGATION WITH PERCEIVED ORGANIZATIONAL SUPPORT AS A MEDIATION VARIABLE - Mardiansyah, Mardiansyah; Hardjo, Suryani; Aisyah, Siti (International Journal of Cultural and Social Science, 2025)
This study aims to analyze influence of work morale on organizational commitment of Police Members of the Directorate of Drug Investigation with perceived organizational support as a mediating variable. Organizational commitment is the willingness of employees in this case the willingness of Polri personnel to prioritize the organization over personal interests, accept the goals and expectations of the organization and make a great contribution to achieving the goals of the Polri organization. This study uses a quantitative method. In this study, the sampling technique used is the total sampling technique. The results of this study indicate that there is an influence of work morale on perceived organizational support of Police Members of the Directorate of Drug Investigation, Aceh Police, the conclusion is based on the value of C.R. (t-statistic) of 6.662> 1.96 and or P-value of *** (0.000 <0.05). There is an influence of perceived organizational support on organizational commitment of Police Members of the Directorate of Drug Investigation of the Aceh Police, the conclusion is based on the value of C.R. (t-statistic) of 3.349 > 1.96 and or P-value with *** (0.000 < 0.05). There is no influence of Work Morale on Organizational Commitment of Police Members of the Directorate of Drug Investigation of the Aceh Police, the conclusion is based on the value of C.R. (t-statistic) of -1.346 < 1.96 and or P-value of 0.178 > 0.05. There is an influence of work morale on organizational commitment with perceived organizational support as a mediating variable for members of the Aceh Police Narcotics Investigation Directorate, the conclusion is based on a mediation test with the Sobel Test, the P-value (Two-tailed) with the Sobel Test is 0.002 <0.05 (significant) and/or with a Sobel t-statistic value of 2.983> 1.96.